Kreativitas Bermusik Bagi Jemaat GPM - Dewi Tika Lestari; Philby Tafuakan; Mercy Halamury; Armando Valentino Makaruku; Ollyvia Sahulata (Batoboh, 2025)
In order to strengthen the implementation of one of the pillars of the Tri Dharma of Higher Education—community service—Institut Agama Kristen Negeri (IAKN) Ambon facilitates the involvement of lecturers and students in a structured service program through the PKM Grant scheme. This program is organized by the Institute for Research and Community Service (LP2M) as an effort to disseminate research findings and scientific works to the community. Through a competitive selection process, selected lecturer- student teams carried out community service activities in designated partner areas, including collaborations with the Protestant Church of Maluku (GPM) in the Masohi and North Ambon Island Classis. The main focus of the activities is to strengthen the capacity of congregations through training based on curriculum and research outcomes, particularly in the development of Indonesian Church Music (Musik Gereja Nusantara). The program is integrated with core subjects such as Minor Compulsory Courses and Church Music Composition in the Master's Program of Church Music Studies. It also aims to create Sunday School songs for church caregivers. These activities are intended to expand the repertoire of church music and enhance the quality of worship through training in vocals, instruments, and music composition. The outcomes of this initiative demonstrate the tangible contribution of higher education in responding to community needs through the collaborative and contextual application of academic knowledge.